A Literature Review on Integrating Enterprise Resource Planning and Supply Chain Management - Sree Martine , T; Amudha, R (International Journal of Engineering and Management Research, 2025)
The Integration of Enterprise Resource Planning (ERP) with Supply Chain Management (SCM) is the key to enhancing the effectiveness and efficiency of supply chains in today's business environment. This paper explores the large body of research into the implementation of ERP systems within SCM and their related functions. It emphasizes the role that ERP plays in achieving operational efficiency and performance enhancement across supply chains. It indicates that the adoption of ERP solutions enhances business performance significantly, which includes better management of production processes, optimum management of inventories, and proper decision-making by enhancing data sharing. This research intends to conduct a systematic review of existing literature on ERP technologies in SCM, answering two primary sub-research questions: the implementation of ERP systems in SCM and the integration between these systems within supply chain processes. The research will be able to analyze numerous scholarly articles in order to identify trends, benefits, and challenges associated with ERP implementation in SCM. This will be invaluable insight for organizations contemplating the adoption of ERP, providing them with knowledge that will enhance their supply chain performance. Finally, this paper contributes to a deeper understanding of how ERP transforms SCM practices and drives competitiveness in an increasingly digitalized industrial landscape.